Aplikasi Ideologi dan Strategi Muhammadiyah Berbasis Android - Dandi Sunardi; Muntahanah; Lodiansah (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
Muslims who have the soul of a believer, muhsin, and mutaqin, who are plenary, are required to have beliefs based on monotheism that are consistent and free from shirk, bid'ah, and superstition. Have a bayani, burhani and irfani way of thinking. Having behavior and actions that are always based on and reflecting good morals which are rahmatan lil 'alamin. Muhammadiyah is an Islamic movement, da'wah movement and tajdid movement based on the Qur'an and Sunnah. A lecturer at the Faculty of Engineering, University of Muhammadiyah Bengkulu, is a member of Muhammadiyah, this is evidenced by the ownership of a Muhammadiyah member card. However, there are still many lecturers who do not have Muhammadiyah Ideology and Strategy books, thus encouraging the authors to develop an Android-based application of Muhammadiyah ideology and strategy. The system development model is the waterfall model. The Muhammadiyah Ideology and Strategy application goes according to plan based on black box testing and obtains a value of 97% from user testing.